High-sensitivity c-reactive protein (hs-CRP)in pre-hypertensive young adults - Ab Samat, Asmak; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; Abdullah, Nor Zamzila; Abdullah, Aszrin (2017)
Hs-CRP is an “acute-phase protein”, intricately sensitive as a systemic marker of inflammation and tissue damage. Its values are recommended as part of the global risk assessment for cardiovascular diseases (CVD) in asymptomatic individuals by the Center for Disease Control and Prevention (CDC) and the American Heart Association (AHA). Hypertension is one of the major risk factors of CVD, usually preceded by pre-hypertension particularly in young adults (18 to 45 years old).Values of hs-CRP differ between populations, therefore identifying levels in the population is crucial as an early predictor to CVD.